Pembelajaran Penemuan yang Dikombinasikan dengan Strategi RQA untuk Memperkuat Literasi Sains dan Keterampilan Berpikir Dasar pada Siswa Sekolah Dasar - Dwi Endah Yulianing Tias; I Wayan Wesa Atmaja; Ahmad Zaki Emyus; Endra Priawasana (Postgraduate, University of Mataram, 2026)
Despite national curriculum reforms emphasizing inquiry-based learning, Indonesian elementary students demonstrate persistently low science literacy and underdeveloped basic scientific thinking skills encompassing observation, classification, prediction, and inference, as evidenced by below-benchmark performance on international assessment results. This quasi-experimental study with a nonequivalent control group pretest-posttest design investigates whether integrating Discovery Learning with the Reading–Questioning–Answering (RQA) strategy effectively enhances these competencies. Conducted across three elementary schools in Jember, East Java, the study involved 120 fifth-grade students (aged 11–12 years) assigned to experimental (n = 60) and control (n = 60) groups based on intact classrooms. The experimental group received Discovery Learning–RQA instruction, while the control group experienced conventional teacher-centered approaches over six 90-minute sessions. Validated instruments measured science literacy (Cronbach's α = 0.82) and basic scientific thinking skills (α = 0.79), supplemented by systematic classroom observations. Results demonstrated that experimental students achieved significantly higher gains in science literacy (M = 20.25 points, a 34.67% increase) and scientific thinking (M = 19.41 points, a 31.22% increase) compared to controls (M = 7.42 and 7.17 points), with very large effect sizes (Cohen's d = 3.005 and 2.711, p < .001). Observational data confirmed elevated engagement in exploration, questioning, active reading, discussion, and drawing conclusions. The findings indicate that integrating constructivist inquiry with metacognitive reading strategies effectively scaffolds both conceptual understanding and procedural competencies essential for elementary science literacy development.